2021
DOI: 10.1108/ijccsm-02-2020-0016
|View full text |Cite
|
Sign up to set email alerts
|

Does ownership type affect environmental disclosure?

Abstract: Purpose In recent years, firms tend to direct their attention in communicating their environmental actions with their stakeholders. However, the level of environmental disclosers varies significantly among firms. This paper aims to explain the variation in environmental disclosure of firms based on their ownership type, namely – state ownership and institutional ownership. The study further aims to understand whether and how the relationship between ownership structure and environmental disclosure changes rega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 36 publications
4
22
2
Order By: Relevance
“…In a similar fashion, Kilincarslan, Elmagrhi, and Li [47] conducted a study to ascertain the influence of corporate governance on environmental sustainability reporting and concluded that proxies of corporate governance are positive and have significant influence on companies' environmental sustainability reporting practices. The findings are in like manner to past studies results [2,13,26,30,40,50,52,67].…”
Section: Review Of Extant Literaturesupporting
confidence: 91%
See 1 more Smart Citation
“…In a similar fashion, Kilincarslan, Elmagrhi, and Li [47] conducted a study to ascertain the influence of corporate governance on environmental sustainability reporting and concluded that proxies of corporate governance are positive and have significant influence on companies' environmental sustainability reporting practices. The findings are in like manner to past studies results [2,13,26,30,40,50,52,67].…”
Section: Review Of Extant Literaturesupporting
confidence: 91%
“…In the same vein, Acar, Çalıyurt, and Zengin-Karaibrahimoglu [2] conducted an empirical study and discovered that companies that have more state ownership have a higher level of environmental disclosures. As well, Rafique, Malik, Waheed, and Khan [73] discovered in their study a favourable nexus between environmental disclosure and directors' independent as well as the board size.…”
Section: Review Of Extant Literaturementioning
confidence: 99%
“…In recent years, the concept of ESG disclosure has become a hot topic not only for academia but also for practitioners and international standard-setters [15][16][17]. Among all the studies, a great part of the extant literature has focused on the impact of ESG disclosure on the firm performance or on how a single pillar of the ESG affects the firm performance [3,18,19].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Insider share is an instrument that aligns the benefits of stockholders and administrators (Acar et al, 2021;Kilincarslan et al, 2020;Akhtaruddin et al, 2009). The concept of agency indicates that when there is different of proprietorship and regulator of a bank, probable agency charges arise due to conflicts of interest among the constricting parties.…”
Section: Shares Held By Insiders and Environmental Reportingmentioning
confidence: 99%
“…There is indication that securities regulators and those setting accounting standards are progressively conscious of the reputation of being communally and ecologically accountable (Sobhani et al, 2009). Previous studies have been conducted on this aspect (Acar et al, 2021;Kilincarslan et al, 2020;Hussain et al, 2018;Samahaa et al, 2015;Janggu et al, 2014;Jizi et al, 2014;Allegrini and Greco, 2013;Ntim et al, 2013;Kathyayini et al, 2012;Haji, 2012;Akhtaruddin and Rouf, 2012).…”
Section: Introductionmentioning
confidence: 99%